Produksi Enzim Fibrinolitik Tempe oleh Rhizopus oryzae FNCC 6078 - Alicia Sada; Noor Erma Sugianto; Achmad Toto Poernomo (Berkala Ilmiah Kimia Farmasi, 2021)
ackground Rhizopus oryzae FNCC 6078 had been evaluated producing fibrinolytic enzyme under solid state fermentation. Soybean had been used to produce fibrinolytic enzyme through fermentation in tempeh. The main purpose of this study was to reveal optimum condition for fermentation. The parameters of the condition were inoculum volume, incubation period and temperature. Optimum condition was defined by maximum fibrinolytic activity. Methode Fibrinolytic activity was measured using spectrophotometry at 274 nm. Result optimum condition for producing fibrinolytic enzyme was 1,5 mL volume of inoculum of Rhizopus oryzae suspension in 25%T, 42 hours for incubation period and 35oC temperature incubation.